PENGARUH RESPON PERUSAHAAN DALAM INVESTASI TEKNOLOGI INFORMASI TERHADAP KINERJA PERUSAHAAN FINANCE DI MANADO - Dajoh, Imelda Anggereiny; Wokas, Heince (ACCOUNTABILITY, 2013)
Financing companies are companies that provide or lend funds to consumers for the purchase of goods - goods such as vehicles, machinery, tools - and other heavy equipment - Other items purchased with a guarantee. Information technology investment is one of the company's assets that could improve the performance of the company in order to achieve company goals. Where technology is defined as the development and application of combining resources and knowledge that can help people solve the problem, while the information is a very important resource as a staple in maintaining the continuity of the company. So the information technology communication lines that carry data, voice and video that have been processed, so it is useful to take a decision that has meaning and is useful to achieve certain goals. Object of this study is a company - a finance company that is in Manado. Study authors are conducting the research is that information technology investments made by finance companies can improve the performance of the company. Based on the research results obtained by a simple linear regression equation between the value of information technology on performance is Y = 0.987 X + ε. This equation gives the sense that if the investment company's response to Information Technology  ( IT )  increases 1 unit, then the performance of the company will increase by 0.987 units .. If the value of β which is the correlation coefficient of the variable response to the company's IT investment  ( X )  of 0.987 means that if the response to the company's IT investment increase by 1 unit then the performance of the company will increase by 0.987 units